2021
DOI: 10.1093/jmammal/gyab014
|View full text |Cite
|
Sign up to set email alerts
|

Home range, habitat selection, density, and diet of golden jackals in the Eastern Plains Landscape, Cambodia

Abstract: We used radiocollars and GPS collars to determine the movements and habitat selection of golden jackals (Canis aureus) in a seasonally dry deciduous forest with no human settlements in eastern Cambodia. We also collected and analyzed 147 scats from jackals to determine their seasonal diet and prey selection. The mean (± SE) annual size of home-range ranges (47.1 ± 2.5 km2; n = 4), which were mutually exclusive between mated pairs, was considerably larger than that previously reported for this species, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This means that the minimum distance between two occurrences in the final data set is at least 50 km. This largely exceeds the home range, which is given with different sizes in the literature, e.g., 11.2 km 2 on average with a range of 1.3–32.5 km 2 according to Fenton et al ( 2021 ) or about 47.1 ± 2.5 km 2 according to Kamler et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 75%
“…This means that the minimum distance between two occurrences in the final data set is at least 50 km. This largely exceeds the home range, which is given with different sizes in the literature, e.g., 11.2 km 2 on average with a range of 1.3–32.5 km 2 according to Fenton et al ( 2021 ) or about 47.1 ± 2.5 km 2 according to Kamler et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 75%
“…Nonetheless, previous studies showed that the occupancy of leopard cats was not affected by the presence of Asian golden cats (Kamler et al 2020a) or jungle cats (Rostro-García et al 2021), indicating leopard cats might not spatially avoid meso-felids. Furthermore, leopard cats were not found in the scats of Asian golden cats (Kamler et al 2020a), jungle cats (Rostro-García et al 2021), and jackals (Kamler et al 2021), indicating this small felid might not be preyed upon frequently by these mesocarnivores. Regardless, we recommend that future studies examine in more detail if mesocarnivores affect the density or occupancy of leopard cats.…”
Section: Discussionmentioning
confidence: 99%
“…Like the biomimetics of symbiosis in nature, [43,54,55] SLSM benefits from the sole function provided by the lichen to regulate the ambient humidity. Without it, the P-type TPMS has absolutely zero capability of absorbing or releasing moisture into its surrounding environment.…”
Section: Meta-symbiotic Moisture Functionmentioning
confidence: 99%